Membangun Kewirausahaan Inovatif Masyarakat Kelurahan Padasuka Kecamatan Cimenyan Kabupaten Bandung - Diah Fatma Sjoraida; Aat Ruchiat Nugraha - (CV. Multi Kreasi Media, 2022)
The purpose of this community service activity is to provide knowledge and skills to the people of Padasuka Village, Cimenyan Kabupaten Bandung District in developing digital entrepreneurial literacy. The main activities were carried out at the Bhakti Asih Islamic Junior/Senior High School Campus and the Padasuka Village Meeting Hall, Cimenyan District, Bandung Regency. The method used is in the form of material presentation, discussion and practice in the form of a simulation of financial management Usaha Mikro Kecil Menengah (MSMEs) as a form of digital entrepreneurial literacy. This activity succeeded in attracting 50 students and 30 MSME actors in the Padasuka Village area. The result obtained from this activity is an increase in public knowledge about digital entrepreneurial literacy througha digital literacy seminar and MSME financial management which is delivered simply and practically. In addition, this financial literacy seminar can improve people's skills in using digital media that supports MSME businesses.